STRATEGI PENINGKATAN NASABAH BANK SYARIAH DENGAN PENDEKATAN EXPERIENTAL MARKETING (STUDI PADA BANK MUAMALAT KCP BONE) - Julianti Putri, Helma; Munawarah, Munawarah (Islamic Banking and Finance, 2022)
The objectives of this study are: (1) to find out how the form of the Experiental Marketing implementation strategy carried out by Bank Muamalat KCP Bone in increasing the number of customers (2) to find out and analyze the constraints of Bank Muamalat KCP Bone in increasing the number of customers through an Experiental Marketing approach and solutions to overcome these obstacles. This type of research is field research with qualitative research methods and descriptive approaches. Data were collected through observation, interviews, and documentation. The data obtained are analyzed using data reduction methods, data presentation and inference. At Bank Muamalat KCP Bone, the form of strategy for implementing Experiental Marketing carried out in increasing prospective customers is by approaching emotionally to prospective customers/ customers, conducting ball pick-up services to prospective customers through the "Ayo Hijrah" program, product promotion through the Muamalat DIN (Digital Islamic Network) Application, building company branding through Sourvenir promotions, collaborating with students in the procurement of Islamic banking training and seminars and find out the background of potential customers. The obstacles that are usually faced are prospective customers who lack respect for the service/arrival of bank employees when providing information, in terms of corporate culture/ organizational culture, and lack of public understanding of Islamic banks. However, these obstacles can be overcome by always following the wishes of prospective customers by doing the best service, evaluating themselves in carrying out organizational culture, and aggressively conducting the "Ayo Hijrah" campaign to invite people to switch to a sharia-based economy.